2023
DOI: 10.3390/ijms241311117
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low-Frequency Electromagnetic Stimulation (ELF-EMS) Improves Neurological Outcome and Reduces Microglial Reactivity in a Rodent Model of Global Transient Stroke

Amanda Moya-Gómez,
Lena Pérez Font,
Andreea Burlacu
et al.

Abstract: Extremely low-frequency electromagnetic stimulation (ELF-EMS) was demonstrated to be significantly beneficial in rodent models of permanent stroke. The mechanism involved enhanced cerebrovascular perfusion and endothelial cell nitric oxide production. However, the possible effect on the neuroinflammatory response and its efficacy in reperfusion stroke models remains unclear. To evaluate ELF-EMS effectiveness and possible immunomodulatory response, we studied neurological outcome, behavior, neuronal survival, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…In a follow-up study on post-stroke patients, they found that exposure to ELF-EMF led to a significant elevation in the levels of growth factors and cytokines associated with neuroplasticity and facilitated a notable improvement in functional recovery (Cichoń et al, 2018). In animal models of transient stroke, the results indicated that exposure to ELF-EMF enhanced the neurological assessment and behavioral outcomes, exhibited a positive impact on neuronal viability, and contributed to a reduction in glial reactivity within the hippocampus, which confirmed the potential of EMF as a clinical therapy (Moya-Gómez et al, 2023).…”
Section: Nervous Systemmentioning
confidence: 83%
“…In a follow-up study on post-stroke patients, they found that exposure to ELF-EMF led to a significant elevation in the levels of growth factors and cytokines associated with neuroplasticity and facilitated a notable improvement in functional recovery (Cichoń et al, 2018). In animal models of transient stroke, the results indicated that exposure to ELF-EMF enhanced the neurological assessment and behavioral outcomes, exhibited a positive impact on neuronal viability, and contributed to a reduction in glial reactivity within the hippocampus, which confirmed the potential of EMF as a clinical therapy (Moya-Gómez et al, 2023).…”
Section: Nervous Systemmentioning
confidence: 83%
“…Accumulating evidence has revealed that glial cells play a pivotal role in cerebral IR injury [ 27 , 28 , 29 ]. Cerebral IR induces the reaction of microglia and astrocytes, as evidenced by the presence of enlarged cell bodies and hypertrophic processes, and they secrete diverse proinflammatory mediators, which contribute to severe neuroinflammatory responses and the aggravation of cerebral IR injury [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%